Considering Structural and Ideological Barriers to Anti‐Poverty Programs in the United States: An Uninhibited, and Unconventional, Analysis. Issue 4 (30th November 2018) - Skidmore, Max J.
Abstract : Historical circumstances and ideological factors combine to obscure the presence and severity of poverty in the United States. Moreover, in recent years, America's two‐party system has become increasingly nonsymmetrical, with a significant segment of the political system devoted to privatization, deferring to demands from religious fundamentalists, and draining power and authority from the government (with the notable exception of police and military powers). The result is continual pressure to shrink government, minimize taxes, reduce or eliminate regulation, enhance the power of private commercial interests, and rely upon citizens to care for themselves without assistance. This has led to a demonization of the "welfare state, " an enormous increase in income inequality, a concentration of wealth upward, a significant effort aimed at largely withdrawing government from the provision of health care, and the retreat of a major political party from acceptance of any obligation to promote the general welfare.